Painting the City Red : Chinese Cinema and the Urban Contract - Braester, Yomi (Book collections on Project MUSE., 2010)
A historical account of how films and theater pieces created in the PRC (and Taiwan) since 1949 have interacted with state and local governments, developers and city planners, and ordinary residents in the dramatic urbanization of China.